Return to emergency department after pediatric urology procedures. Issue 1 (February 2019) - Naoum, N.K.; Chua, M.E.; Ming, J.M.; Santos, J.D.; Saunders, M.A.; Lopes, R.I.; Koyle, M.A.; Farhat, W.A.
Summary: Background: Unplanned postoperative return visits to the emergency department (ED) and readmission represent a quality bench outcome and pose a considerable cost burden to health-care systems. Objective: The aim of this study is to evaluate ED return visits after pediatric urology procedures in a tertiary care children's hospital, trying to identify potential causes. This may constitute a platform for future improvement areas. Materials and methods: A Quality Board–approved retrospective study was performed identifying all urologic cases completed between October 2012 and September 2015. Baseline demographics, American Society of Anesthesia class, operating surgeon, type of admission, type and duration of surgical procedure, and type of anesthesia given were evaluated. Patients who returned to the ED within 30 days of the surgery date were identified. The ED records were reviewed for time of return, etiology for visit, and management received. Univariate and subsequent multivariate logistic regression statistical analyses were performed to identify variables associated with ED return. Odds ratio (OR) and 95% confidence intervals (95% CIs) were generated to determine the significance of relationships. Results: Total of 4125 cases was identified. Median age was 32.9 months, with 85.1% of them being male. 349 (8.5%) cases returned to the ED within 30 days of the surgery. The majority of the returned patients, 295 (84.5%), managed conservatively with medications or reassurance, whereas 54 (15.5%) required readmission, and of those readmitted, 15 (4.3%) cases needed further surgical interventions, mainly urinary tract drainage procedures. Multivariate logistic regression analysis identified that the age, residence, admission type, inguinoscrotal surgery, and duration of surgical procedure were significantly associated with ED return (Table). The most common reason for the ED visit was UTI in 17.2%, followed by stent and catheter issues in 14.3%, wound-related in 14.3%, and bleeding in 11.7%. Discussion: Pediatric literature show varying rates of ED return ranging from 2.4% to 2.6% after urologic procedures. Our return to ED rate exceeds that found in US studies, which can perhaps be attributed to the differences between the Canadian and US health-care systems. As found with other studies, age, inpatient admission, procedure type, and increased operative time were related to ED returns, possibly because of the difficulty of young children expressing themselves and the presumed complex nature of longer operations that mostly need inpatient admission. The most common reason for ED return in this study as in others was presumptive UTI. A known limitation of this study is its retrospective nature, along with the possible missed visits of patients who presented to outside hospitals. Conclusion: We present an account of the status of ED return visits after pediatric urology procedures in our institute. The majority of ED returns can be managed conservatively and are probably preventable. ED return variables p-value Odds ratio 95% CI for odds ratio Lower Upper Gender: Female 0.932 1.016 0.707 1.459 Age in month 0.002 0.997 0.995 0.999 Residence in Toronto <0.001 2.171 1.700 2.772 Admission type: inpatient 0.010 1.487 1.100 2.009 Endoscopic procedures 0.707 1.108 0.648 1.896 Penile procedures 0.989 0.997 0.640 1.553 Inguinoscrotal procedures <0.001 0.298 0.177 0.501 Upper tract procedures 0.369 0.766 0.429 1.369 Lower tract procedures 0.873 1.052 0.566 1.955 Duration of surgical procedures (minutes) 0.005 1.002 1.001 1.003